Penerapan Sistem Informasi Akuntansi Persediaan Pada Supermarket (Studi Kasus Suzuya Supermarket di Rantau Prapat) - Gustrianingsih G; Saparuddin Siregar; Wahyu Syarvina (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Trading companies generally use and require an inventory accounting system to find out the stock and price of the goods of sale. This research is aimed at finding out the application of the information system of inventory accounting in the Suzuya Supermarket, with a qualitative descriptive approach. But it needs to be fixed because there is a difference in the amount of physical supplies in the warehouse and in the computer system, the physical inspection of the stock of goods only once in six months. Although training has been conducted, the qualification on human resources has not been met.